Insights Regarding the Role of Inflammasomes in Leukemia: What Do We Know? - Fabíola Silva Alves-Hanna; Juniel Assis Crespo-Neto; Glenda Menezes Nogueira; Daniele Sá Pereira; Amanda Barros Lima; Thaís Lohana Pereira Ribeiro; Vitória Giovanna Rodrigues Santos; Joey Ramone Ferreira Fonseca; Fábio Magalhães-Gama; Aya Sadahiro; Allyson Guimarães Costa (Journal of Immunology Research)
Inflammation is a physiological mechanism of the immune response and has an important role in maintaining the hematopoietic cell niche in the bone marrow. During this process, the participation of molecules produced by innate immunity cells in response to a variety of pathogen-associated molecular patterns and damage-associated molecular patterns is observed. However, chronic inflammation is intrinsically associated with leukemogenesis, as it induces DNA damage in hematopoietic stem cells and contributes to the creation of the preleukemic clone. Several factors influence the malignant transformation within the hematopoietic microenvironment, with inflammasomes having a crucial role in this process, in addition to acting in the regulation of hematopoiesis and its homeostasis. Inflammasomes are intracellular multimeric complexes responsible for the maturation and secretion of the proinflammatory cytokines interleukin-1β and interleukin-18 and the cell death process via pyroptosis. Therefore, dysregulation of the activation of these complexes may be a factor in triggering several diseases, including leukemias, and this has been the subject of several studies in the area. In this review, we summarized the current knowledge on the relationship between inflammation and leukemogenesis, in particular, the role of inflammasomes in different types of leukemias, and we describe the potential therapeutic targets directed at inflammasomes in the leukemic context.